THE TRANSLATION OF RELIGIOUS TERMS IN SAODAT ASRI QISSALARI (Multidisciplinary Journal of Science and Technology, 2025)
Religious words are more than just vocabulary. They carry emotion, belief, and deep cultural meaning. In this paper, I explore how five Islamic terms from the Uzbek translation of Saodat Asri Qissalari can be translated into English while keeping their original spirit. Following Eugene Nida’s approach of dynamic equivalence, I focus on meaning and emotional impact rather than word-for-word accuracy. Some terms worked best with short explanations, others with familiar English phrases, and in some cases, keeping the original word made more sense. The main goal is to help English readers connect with the text in the same way Uzbek readers do, whether through a sense of respect, irony, or spiritual reflection.